Signal Conditioning in Process of High Speed Imaging - Libor Hargas; Dusan Koniar; Anna Simonova; Miroslav Hrianka; Zuzana Loncova (Advances in Electrical and Electronic Engineering, 2015)
The accuracy of cinematic analysis with camera system depends on frame rate of used camera. Specific case of cinematic analysis is in medical research focusing on microscopic objects moving with high frequencies (cilia of respiratory epithelium). The signal acquired by high speed video acquisition system has very amount of data. This paper describes hardware parts, signal condition and software, which is used for image acquiring thru digital camera, intelligent illumination dimming hardware control and ROI statistic creation. All software parts are realized as virtual instruments.